Assistance for Pregnant Women in The III Trimester and Delivery Companion in Carrying Out Oxytocin Massage in Jati Perumnas Village, Kalumata Puskesmas Working Area (International Journal of Scientific Research and Management (IJSRM), 2023)
Jati Perumnas Village is one of the working areas of the Kalumata Community Health Center which is located in South Ternate District. Based on data in PMB Bd. The number of births in 2022 will be 14 people and 5 cases will be referred to due to prolonged labor. At the time of delivery, part of the mother’s back was rubbed, but no assistance or counseling was given about the importance of oxytocin massage for pregnant women in the third trimester. To overcome this problem, the service provides assistance to pregnant women in the third trimester and the people closest to the pregnant mother who are birthing companions (husband, parents, in-laws, etc.) in carrying out oxytocin massage. The target partners for this service are third trimester pregnant women and birth companions. The results of the service are increased knowledge, the ability to perform oxytocin massage increases for the companion. The person who does the massage is the companion, but if the pregnant woman doesn’t know, she will not ask for a massage so that there is synergy between the pregnant mother and her companion. Birth companions are prepared to be independent in massaging and also strengthen pregnant women’s knowledge that massage is needed to facilitate the birth process later.